Dynamic Response of Ionospheric Plasma Density to the Geomagnetic Storm of 22‐23 June 2015. Issue 8 (17th August 2019) - Ngwira, Chigomezyo M.; Habarulema, John‐Bosco; Astafyeva, Elvira; Yizengaw, Endawoke; Jonah, Olusegun F.; Crowley, Geoff; Gisler, Andrew; Coffey, Victoria
Abstract: On 21–22 June 2015, three consecutive interplanetary shocks slammed into the Earth's magnetosphere. Immediately after the third shock at 18:36 UT on 22 June, marked by an exceptional sudden storm commencement with an amplitude of ΔSYM‐H = ∼106 nT, a major geomagnetic storm commenced. In the present study, a multi‐instrument approach comprising observations, data analysis, and modeling is used to examine the global ionospheric response. Results show that enhanced storm time processes produced major total electron content (TEC) variations at different latitudes, longitudes, and phases of the storm. A closer inspection of the TEC observations reveals strong longitudinal and hemispherical asymmetry. In addition, multiple equatorward and poleward propagating traveling ionospheric disturbances (TIDs) were detected in the TEC data. Equatorward propagating TIDs are consistent with vertical neutral winds simulated from Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model; however, poleward TIDs were not reproduced in the model. We find that a combination of driving processes including enhanced high‐latitude injection, prompt penetration electric fields, disturbance dynamo effect, neutral winds, and composition changes were acting at different stages of the storm. Key Points: We investigate strong global total electron content (TEC) variations observed during the June 2015 geomagnetic storm For the first time, multiple equatorward and poleward TIDs were observed and reported during this major storm Excitation of equatorward TIDs associated with enhanced high‐latitude injection, however, poleward TIDs were not captured by TIE‐GCM model